(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Development always implies some vision of good life and choice of preferred means for moving towards it. Development is a multidimensional process. Indian economy has traditionally been and under developed economy, where 70 of the population is dependent on agriculture as their primary source of livelihood. Significantly land is the most essential asset for the development and growth of any Nation, particularly in the infrastructure sectors. To fulfil the said objective, the Government has to acquire the land under the Land Acquisition Act, 1894 and other nineteen special Acts, which are applicable to various other sectors including Highways, Railways, Ports and Defence. Hindu Succession Act, 1956 provide equal property rights to women in ancestral property. Earlier girls used to enjoy this right before marriage but this Act help her to enjoy this right even after getting married. Time is changing so is the position of women in the society. Now women are more educated and independent. What is her position in family, the moment she exercise her rights? How her relations with parents, siblings and society as a whole changes after taking share in the family property? This is what I explored in my present study of a Village called Nawada Fatehpur in District Gurugram. It is important to understand the ground reality of women special when they exercise their rights because mere provisions of such rights on paper would not change her position.